2017
DOI: 10.1021/acsami.7b09801
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Fabrication of Hierarchical Frameworks with Tuned Pore Structure and N,O-Co-Doping for High-Performance Supercapacitors

Abstract: A series of multiheteroatom porous carbon frameworks (MPCFs) is prepared successfully from the trimerization of cyano groups of our designed and synthesized 4,4'-(4-oxophthalazine-1,3(4H)-diyl)dibenzonitrile monomers and subsequent ionothermal synthesis. Benefiting from the molecular engineering strategy, the obtained MPCFs framework show a homogeneous distribution of nitrogen and oxygen heteroatoms at the atomic level, confirmed by the transmission electron microscopy mapping intuitively, thereby ensuring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 60 publications
1
44
0
Order By: Relevance
“…The CV curves all had rectangular shapes, even when recorded at the highest scan rate of 200 mV s −1 , suggesting capacitive behavior with a high rate performance suitable for use in supercapacitors . The distinct appearance of humps in the rectangular CV curves revealed that the capacitive response was derived from a combination of electric double‐layer capacitance (EDLC) and pseudocapacitance arising from the presence of heteroatoms (i.e., nitrogen and oxygen atoms) . Figure b provides galvanostatic charge‐discharge (GCD) curves of the TPT‐DAHQ COF recorded at various current densities, from 0.5 to 20 A g −1 .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…The CV curves all had rectangular shapes, even when recorded at the highest scan rate of 200 mV s −1 , suggesting capacitive behavior with a high rate performance suitable for use in supercapacitors . The distinct appearance of humps in the rectangular CV curves revealed that the capacitive response was derived from a combination of electric double‐layer capacitance (EDLC) and pseudocapacitance arising from the presence of heteroatoms (i.e., nitrogen and oxygen atoms) . Figure b provides galvanostatic charge‐discharge (GCD) curves of the TPT‐DAHQ COF recorded at various current densities, from 0.5 to 20 A g −1 .…”
Section: Figurementioning
confidence: 99%
“…Figure b provides galvanostatic charge‐discharge (GCD) curves of the TPT‐DAHQ COF recorded at various current densities, from 0.5 to 20 A g −1 . The GCD curves display triangular shapes with a slight bend, implying the existence of both EDLC and pseudocapacitance arising from heteroatoms (i.e., nitrogen and oxygen atoms) . The specific capacitance was calculated from the GCD curves using equation (S1) as shown in Figure c. The TPT‐DAHQ COF exhibited excellent specific capacitance of 256 F g −1 at current density of 0.5 A g −1 which was decreased to 131 F g −1 when the current density was increased to 20 A g −1 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Graphene, a two‐dimensional single‐atom‐layer carbon material with a high specific surface area as high as 2630 m 2 /g and good electrical conductivity induced by covalently bonded sp 2 carbon atoms, is regarded as one of the most attractive candidate electrode materials of supercapacitors. However, compared with other energy storage devices, graphene supercapacitors exhibit low specific capacitance …”
Section: Figurementioning
confidence: 99%
“…Some multi‐heteroatom porous carbon frameworks (MPCFs) were prepared successfully by the trimerization of cyano groups of the synthesized 4,4′‐(4‐oxophthalazine‐1,3(4H)‐diyl) dibenzonitrile (OPDN) monomers and subsequent ionothermal synthesis . In the prepared MPCFs framework, nitrogen and oxygen heteroatoms exhibited a homogeneous distribution at the atomic level, hence ensuring the stability of electrical performance for MPCFs.…”
Section: Applications Of Cofs In Supercapacitorsmentioning
confidence: 99%